2008
DOI: 10.1038/onc.2008.45
|View full text |Cite
|
Sign up to set email alerts
|

Isosilybin B causes androgen receptor degradation in human prostate carcinoma cells via PI3K-Akt-Mdm2-mediated pathway

Abstract: The identification and development of novel nontoxic phytochemicals that target androgen and androgen receptor (AR) signaling remains a priority for prostate cancer (PCA) control. In the present study, we assessed the antiandrogenic efficacy of isosilybin B employing human PCA LNCaP (mutated AR), 22Rv1 (mutated AR) and LAPC4 (wild-type AR) cells. Isosilybin B (10-90 lM) treatment decreased the AR and prostate specific antigen (PSA) levels in LNCaP, 22Rv1 and LAPC4 cells, but not in non-neoplastic human prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
(51 reference statements)
4
50
0
Order By: Relevance
“…Earlier findings [20], [21], [22], [24] and the present study suggested that among the four pure flavonolignans, isosilybin B is the most effective in terms of efficacy against PCA cells but, surprisingly, it has the least efficacy in terms of its effect on HUVEC (inhibition of chemotactic motility or apoptosis induction) (Figs. 6 and 7).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Earlier findings [20], [21], [22], [24] and the present study suggested that among the four pure flavonolignans, isosilybin B is the most effective in terms of efficacy against PCA cells but, surprisingly, it has the least efficacy in terms of its effect on HUVEC (inhibition of chemotactic motility or apoptosis induction) (Figs. 6 and 7).…”
Section: Resultssupporting
confidence: 63%
“…Therefore, we rationalized the need to identify non-toxic natural agents with broad spectrum anti-angiogenic efficacy; and in this regard, in the present study, we focused on the anti-angiogenic efficacy of four pure diastereoisomers from Milk Thistle ( Silybum marianum ) extract, namely silybin A, silybin B, isosilybin A and isosilybin B. These diastereoisomers are flavonolignans with an identical flavonoid moiety and differ only in their configurations about the lignan moiety, and their chemical and biological properties have been detailed earlier [20], [21], [22], [23], [24]. Here, for the first time we analyzed the angiopreventive efficacy of these flavonolignans in PCA xenograft model and various ex vivo , in vivo and in vitro angiogenesis assays.…”
Section: Introductionmentioning
confidence: 99%
“…22Rv1 cells, although less sensitive to ISA-2011B, also displayed reduced proliferation after ISA-2011B treatment. It is known that 22Rv1 cells also have relatively high levels of pAKT and AR (37). Given that amplification of AKT2 or mutations in PIK3CA, in addition to PTEN mutation, are all responsible for activation of PI3K pathway (15,38,39), our data suggest that ISA-2011B exerts its on-target effect on PCa cells by targeting pathways related to AKT/AR, rather than a toxic effect.…”
Section: Discussionmentioning
confidence: 73%
“…It must be underlined that silymarin can also bind the androgen receptor, and it activates the same molecular pathways involved in the ERβ signaling, specifically in prostate cancer cells (205, 206). However, the expression and the possible role of this receptor in skin carcinogenesis is still a matter of debate (60, 107, 207, 208).…”
Section: Natural Erβ Ligands and Melanomamentioning
confidence: 99%